Analisis Pemanfaatan Aplikasi E-Rongsok Berbasis Android menggunakan Fitur Lokasi Terdekat dan Notifikasi Realtime dalam Proses Jual Beli Rongsokan - Ismanto, Bambang; Amalia, Nurul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Nowadays, businesses buying and selling used goods are popping up because of government programs to reduce waste, resulting in an increase in demand for used goods for the recycling process. From the business process of selling used goods, it takes quite a long time to wait for people to buy used goods, so the goods require a lot of space to store them, these used goods can also make the house dirty and can cause disease. Meanwhile, collectors also have to wait for used goods from scavengers to meet a certain amount so they can be sent to buyers, thus causing suboptimal business processes. The aim of this research is to analyze the use of the Android-based E-Rongsok application to simplify and speed up the process of buying and selling junk. The research method used in this research goes through several stages, namely preliminary research, system analysis, system design, system development and system testing. From the results of the research carried out, using this application can speed up and make it easier for people to sell junk goods, so that they don't pile up at home, speed up and make it easier for collectors to collect scrap so they can increase deliveries to the recycling industry, notify them via real-time notifications to collectors. The closest thing is if there are people who sell junk goods.